The effect of mineral fertilizers and liming on the properties of sod-podzolic soils and the productivity of legume-grass mixture in the conditions of the Komi Republic - N. T. Chebotaryov; O. V. Brovarova (Аграрная наука Евро-Северо-Востока)
The research was carried out in 1998-2018 in the conditions of the Komi Republic. Under study was the effectiveness of single application (1983) of lime doses (1.0; 2.0; 2.5 h. a.) and the systematic use of mineral fertilizers (N60P75K75) against the background of lime effect in the cultivation of perennial grass mixtures (meadow clover, meadow timothy and cocksfoot). High efficiency was shown by liming at doses of 2.0 and 2.5 h. a., the effect remained for 35 years since their introduction to the soil. Thus, in 2018, the exchange acidity was 4.5-4.8 pHKCl (the initial 4.1-4.2 pHKCl). A similar decrease was observed in the hydrolytic acidity and the content of exchangeable aluminum in the soil. The amount of humus by 2018 increased to 1.7-1.8 % (the initial 1.4-1.5 %). The average yield of perennial grasses during soil liming at doses of 2.0 and 2.5 h .a. was 24.0-25.1 t/ha of green mass (5.3-5.5 t/ha of good quality dry matter), which is 52.8-59.8 % higher than the variant without fertilizers (15.7 green mass and 3.7 t/ha of dry matter). In the variant with the systematic use of NPK, the exchange acid content of the soil and the humus content remained at the initial level, the amount of the mobile forms of phosphorus and potassium increased to 198 and 121 mg/kg of soil (the initial 42 and 62 mg/kg). The average annual yield of grasses was 25.3 t/ha of green mass (5.4 t/ha dry matter) and was 61.1 and 45.9 % higher than the control. Against the background of the aftereffect of lime flour, the effect of NPK on soil properties was similar to the effect of non-fertilizing cultivation, with the exception of a significant increase in the availability of mobile forms of phosphorus and potassium – up to 254-288 and 148-166 mg/kg, respectively. A high yield of green mass of 28.1-30.7 t/ha (6.4-6.7 t/ha dry matter) was obtained, exceeding the control by 78.9-95.5 %. In these variants, grass mixture of high quality was obtained: the content of crude protein – 13.8-13.9 %; dry matter – 21.8-21.9 %; the content of total phosphorus – 0.92-0.94 %; potassium – 2.93-2.95 % and calcium – 0.79-0.81 %. The amount of nitrates in the feed did not exceed the MPC (147-149 mg/kg dry matter). Long-term studies on sod-podzolic poorly cultivated soil showed that the optimal method for the cultivation of long-term legume-cereal grass mixture was the use of lime flour (2.0 and 2.5 h .a.) and the annual use of N60P75K75.